A Feasibility Study on the Establishment of Fruit Shake “Pealicious” in Four M Square Building, Greater Lagro, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The researchers recognize the potential of a business about peanut to arise in the growing food and beverage industry. A peanut is a legume crops grown underground, also known as being important to both small and large commercial producers. It is classified asboth a grain legume and, because of its high oil content, an oil crop. This research focused on a food stall business who sells cool flavored drink mix with peanut milk. The drinks uniqueness and the variety of flavors it offers broadens its appeal to thecustomers and make them interested to try the products. The researchers decide to put a business about peanut namely Pealicious, because peanut has a vitamin that helps the immune system of the Filipino customers.It is not easy to put this kind of business because many companies are locally known and already established brand in the food and beverage industry. The researchers decided to conduct a survey to know if this kind of business can make it to the market. Based from the survey conducted, the respondents answered 20% of the conducted survey that they always drink shake, 62% sometimes, 8% occasionally, and 10% never drink shake. The researchers recognize the potential of this business about peanut to arise in the growing food and beverage industry. The supply increases due to the inflation rate. The products are sometimes seasonal due to the ever-changing weather and your target market wants a uniqueness of product like ours. Make a promo to attract customers especially on those seasons that the product is not that much marketable and conduct a survey to the area to know your target market wants.
Keywords: peanut, growing food and beverage industry, peanut milk